RECURRENT CROUP IN CHILDREN - S. L. Piskunova; A. V. Gordeets; A. A. Chernikova (LLC "Diagnostics and Vaccines", 2015)
The article presents the results of examination of 1849 children, entering children's infectioushospitalofVladivostokwith the clinical picture of croup of viral etiology. The clinical features of primary and recurrent croup are described. Frequency of recurrent croup inVladivostokis 8%. Children with a recurrent croup had the burdened premorbid background, and also persistent herpetic infections (cytomegalic infection in 42,9% cases, cytomegalic infection in combination with the herpes simplex virus -1). Frequency of croups substantially rose in the period of epidemic of influenza.